A Critique of Functionalist Definitions of Art - Fokt, Simon (Kultura-Społeczeństwo-Edukacja, 2015)
This paper deals with the issue of definition of art and artwork in the sense of functionalist approach. It critically argues with the existing terms and meanings of artwork in that sense and presents them as insufficient and inadequate when speaking of modern art. Furthermore functionalism assumes that a great deal of artworks has a specific function, what we cannot say about a large number of contemporary artistic endeavors. Therefore it is being argued here that this approach, how popular it might have been in the past, must be replaced with a new paradigm of comprehension of esthetics.